Self-perceived Weight and Mortality in Korean Adults Based on the Korea National Health and Nutrition Examination Survey Data Linked to Cause of Death Statistics - Kayoung Lee (Journal of Obesity & Metabolic Syndrome, 2022)
Background : This study aimed to determine the associations between self-perceived weight, weight perception, and mortality risk among Korean adults. Methods : Data from the 2007 to 2015 Korea National Health and Nutrition Examination Survey and the 2007 to 2019 Cause of Death Statistics were linked for this cohort study. A complex samples Cox regression analysis involving 42,453 participants (17,056 male; 25,397 female) was performed after excluding those who died within 1 year of the follow-up period, those with a history of cancer, those with cardiovascular diseases, those without body mass index (BMI) data, and those without self-perceived weight data. Results : During 7.85 years of follow-up, the overall mortality rate was 3.8% (4.5% for male and 3.1% for female). Self-perceived thin weight status was associated with a 43% to 68% higher risk of all-cause mortality and a 2.48-times higher risk of cardiovascular mortality compared to self-perceived just right weight status after controlling for sociodemographic characteristics, health-related behaviors, underlying health status, BMI, and metabolic syndrome. After adjusting for the confounding factors, those who underestimated their weight had a 27% reduced risk of all-cause mortality than those who correctly estimated their weight. The risks of all-cause mortality and cardiovascular mortality were 2.14-times higher and 2.32-times higher, respectively, in the underweight group with an accurate weight estimation than in the normal weight group with an accurate weight estimation. However, all-cause mortality was 47% lower among participants with obesity who overestimated their weight. Conclusion : Self-perceived thinness and accurately perceived underweight status were associated with increased risks of all-cause mortality and cardiovascular mortality among Korean adults.